2016
DOI: 10.1111/coa.12725
|View full text |Cite
|
Sign up to set email alerts
|

Voice and ageing: clinical, endoscopic and acoustic investigation

Abstract: We described the vocal symptoms, vocal perceptual and acoustic analysis and endoscopic findings of an elderly population, characterising the presbyphonia. Therapeutic measures must involve speech therapy and/or surgery to reduce the glottal gap, allowing less air leakage and, consequently, better vocal performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
1
26
0
4
Order By: Relevance
“…The decrease in F 0 found in the literature is justified by the anatomic and hormonal changes taking place in the human larynx 8,12,19 , as age advances. Other studies, however, have not observed difference in F 0 values when comparing the voice of young and old women 24,25 , even though the F 0 is the acoustic parameter that changes most with aging 24 . In relation to the male population, most of the studies found do not point to acoustic changes in the voice of elderly men in relation to the younger ones 8,19,24,26 .…”
Section: Literature Reviewmentioning
confidence: 86%
See 3 more Smart Citations
“…The decrease in F 0 found in the literature is justified by the anatomic and hormonal changes taking place in the human larynx 8,12,19 , as age advances. Other studies, however, have not observed difference in F 0 values when comparing the voice of young and old women 24,25 , even though the F 0 is the acoustic parameter that changes most with aging 24 . In relation to the male population, most of the studies found do not point to acoustic changes in the voice of elderly men in relation to the younger ones 8,19,24,26 .…”
Section: Literature Reviewmentioning
confidence: 86%
“…Other studies, however, have not observed difference in F 0 values when comparing the voice of young and old women 24,25 , even though the F 0 is the acoustic parameter that changes most with aging 24 . In relation to the male population, most of the studies found do not point to acoustic changes in the voice of elderly men in relation to the younger ones 8,19,24,26 . Nevertheless, Dehqan et al 9 observed the increase of F 0 in elderly men when compared to adults, due to the reduction in muscle tissue affecting the male larynx in old age.…”
Section: Literature Reviewmentioning
confidence: 86%
See 2 more Smart Citations
“… 9 - 12 As for the vocal characteristics in the elderly, there is unstable voice, increase of the duration of articulatory pauses and speech rate reduction in voice; more breathy voice and of weak intensity, reduction of maximum phonation times. 13 - 16 Men and women may present anatomical differences in aging, such as edema in the female vocal folds, reducing the arch and incomplete glottal closure 9 and generate differences in vocal quality, as well as reduction in fundamental frequency in women 17 and an increase of such in men. 13 Vocal changes may be some of the factors that lead the elderly population to seek health services, noting, therefore, that the vocal conditions affect the overall quality of life of the elderly.…”
Section: Introductionmentioning
confidence: 99%